Single tier tax system: analysis of company dividend payouts - Ismail, Ida Suriya; Palil, Mohd Rizal; Ramli, Rosiati; Che Abdul Rahman, Mara Ridhuan; Mohd Saat, Nur Ashikin (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
The aim of this paper is to analyze company dividend payouts from two observation periods; during transitional period of STT (2008-2013) and after the compulsory effects of STT (2014-2015). Therefore, three research questions need to be tested. Firstly, whether a company pays higher dividend during transitional period compared to before transitional period. Secondly, whether a company pays higher dividend after the compulsory effects of STT compared to before compulsory effects of STT. Lastly, is there any significant difference between top, moderate and low performance companies in their pattern of dividend payouts. Based on a sample of 1,824 observations, it was found that dividend payouts were differently governed between the two periods. Initially, during the transitional period, results were consistent with clientele theory when it was found that there was significantly increase in dividend payouts specifically regular dividend. However, after the compulsory effects of STT, companies reduced their dividend payouts but the difference was insignificant. This study also found that there is significant difference between top, moderate and low performance companies in their pattern of dividend payouts in which top companies had constantly higher dividend payouts than moderate and low companies.